Стратегії й методи вдосконалення автоматичного морфологічного анотування Корпусу української мови - Лангенбах, Маргарита (Видавництво Львівської політехніки, 2017)
The article reviews the typical problems of the dictionary-based part-of-speech tagging. The main attention is focused on the non-recognized words. The experiment is based on the textual samples derived from the Corpus of the Ukrainian Language. The examples were classified by the specific features. The article suggests the strategy of increasing the efficiency of the dictionary-based part-of- speech tagger.
Keywords: автоматичний морфологічний аналіз; машинна морфологія; АГАТ; графемний аналіз; словниковий морфологічний аналіз